Analisis faktor-faktor yang mempengaruhi ekspor pakaian jadi Indonesia ke negara Jepang tahun 1990-2013 - lovely, Vitiya; Natha, Ketut Suardhika (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 5, Mei 2016 (pp. 530-651), 2016)
Indonesia is rich in natural resources and population, has a great opportunity to produce a commodity that is good. One of the dominant Indonesian commodities in the non-oil sector is apparel. Volume and value of apparel exports in the world market continued to increase from year to year so that it can be said as a prima donna apparel exports to Indonesia. This study aims to determine the effect of price, GDP and the exchange rate of the dollar simultaneously and partially on the volume of exports, which dominates the variable export volume and its development prospects. The result is that prices, gross domestic product (GDP) and the US dollar exchange rate simultaneously influence the Indonesian garment exports to Japan in 1990-2013 Country. Price partially positive effect on export volumes, while gross domestic product (GDP) and the US dollar exchange rate partially no effect on the price ekspor. The variable price is known as the most dominant and prospects for the development of Indonesian garment exports to the country of Japan increased in 2014 to 2016.
Keywords: export volumes, prices, gross domestic product, the US dollar exchange rate